Cross sections for single and double electron capture from He++ on hydrogen, neon and argon. - Baragiola, R. A.; Nemirovsky, I. B. (North holland publisher, 1973)
Fil: Baragiola, R. A. Comisión Nacional de Energía Atómica; Argentina